A century defending the child's right to play: beginnings of the playground movement in Melbourne, Australia. (29th April 2016) - Chancellor, Barbara
Abstract : This article explores archival material and historical accounts related to the beginnings of the playground movement in Australia. While this mostly comprises adult perceptions of children in early 1900s Melbourne, occasional glimpses of children's perspectives colour the picture as their playfulness echoes through the years. The terrain of early Melbourne is surveyed, with a mapping of the territories of children as they carve out places to play, shining a light on the vigorous campaign to promote play(work) in an emerging colonial society by the Guild of Play, formed in 1913. Working with children's geographies, comparisons are made between social and moral geographies as they relate to governmentality and play(work) provision in Melbourne 100 years ago and today.